Complete nucleotide sequence of Alfalfa mosaic virus isolated from alfalfa (Medicago sativa L.) in Argentina - Trucco, Veronica Milagros; De Breuil, Soledad; Bejerman, Nicolas Esteban; Lenardon, Sergio Luis; Giolitti, Fabian (Springer, 2018)
The complete nucleotide sequence of an Alfalfa mosaic virus (AMV) isolate infecting alfalfa (Medicago sativa L.) in Argentina, AMV-Arg, was determined. The virus genome has the typical organization described for AMV, and comprises 3,643, 2,593, and 2,038 nucleotides for RNA1, 2 and 3, respectively. The whole genome sequence and each encoding region were compared with those of other four isolates that have been completely sequenced from China, Italy, Spain and USA. The nucleotide identity percentages ranged from 95.9 to 99.1 % for the three RNAs and from 93.7 to 99 % for the protein 1 (P1), protein 2 (P2), movement protein and coat protein (CP) encoding regions, whereas the amino acid identity percentages of these proteins ranged from 93.4 to 99.5 %, the lowest value corresponding to P2. CP sequences of AMV-Arg were compared with those of other 25 available isolates, and the phylogenetic analysis based on the CP gene was carried out. The highest percentage of nucleotide sequence identity of the CP gene was 98.3 % with a Chinese isolate and 98.6 % at the amino acid level with four isolates, two from Italy, one from Brazil and the remaining one from China. The phylogenetic analysis showed that AMV-Arg is closely related to subgroup I of AMV isolates. To our knowledge, this is the first report of a complete nucleotide sequence of AMV from South America and the first worldwide report of complete nucleotide sequence of AMV isolated from alfalfa as natural host.